Influence of coatings on microstructure and mechanical properties of preceramic paper-derived porous alumina substrates - Junkes, Janaína Accordi; Dermeik, Benjamin; Gutbrod, Björn; Hotza, Dachamir; Greil, Peter; Travitzky, Nahum (Journal of Materials Processing Technology, 2013)
Preceramic papers loaded with inorganic fillers may be used as preforms in a novel manufacturing technique to fabricate lightweight ceramic structures. In order to reduce the porosity caused by burning out cellulosic fibers and organics, porous preceramic paper-derived alumina substrates were post-treated via two different coating routes using silica suspension or methylphenylvinylhydrogen polysiloxane. Sintering of the alumina-filled preceramic papers in air at 1600 °C for 2 h resulted in a non-uniform distributed open porosity ranging from 23 to 26%. After coating and infiltration, all samples were additionally heat treated up to at 1500 °C for 2 h. Thermal analysis (DTA/TG) was applied to determine the pyrolysis temperature of polysiloxane. Microstructure and phase analysis were performed respectively by SEM and XRD. After sintering, water absorption, apparent density and open porosity of test pieces were determined, and mechanical properties of the substrates were evaluated before and after coating. For the samples coated with silica suspension, the mechanical strength remained in the same range of those for uncoated samples, while for the polysiloxane coated samples the mechanical strength steadily increases after repeated impregnation steps, reaching 350 MPa.
Keywords: Preceramic paper; Coating; Infiltration; Mechanical properties; Alumina; Silica

PRECERAMIC PAPER DERIVED FIBRILLAR CERAMICS - Gomes, Cynthia M.; Gutbrod, Björn; Travitzky, Nahum; Fey, Tobias; Greil, Peter (Ceramic Transactions, 2010)
Preceramic paper may serve as a preform to manufacture light weight as well as multilayer ceramic products. Fiber reinforced preceramic paper was prepared from bioorganic pulp Fibers, alumina fibers and ceramic fillers. After filtration, pressing and drying the preceramic paper sheet was processed into single sheet and multilayer components. Applying well established paper processing technologies including laminated object manufacturing lightweight ceramic structures of variable shape, size, and complexity may easily be achieved offering a high potential for economical production process based on preceramic paper.